2023
DOI: 10.31004/obsesi.v7i1.3909
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Problem Based Learning Model to Improve Early Childhood Abilities in Creative Thinking

Abstract: The study below examines the development of students' critical and creative thinking abilities through the use of article reviews and the Problem Based Learning instructional approach. This study is qualitative and was conducted utilizing library research, specifically library research that used data grouping methods. It was then completed by examining and studying numerous pertinent research publications and papers. utilizing analytical methods for gathering, combining, and recognizing secondary data from num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…An Technological Literacy on Virus Material JEP (Jurnal Eksakta Pendidikan) |Vol 7| No 2| 185-196 increase was obtained from the average results of creative thinking skills with the application of conventional learning of 64.07, while the application of Problem Based Learning amounted to 75.81. Other research also states that PBL can develop students' creative thinking skills (Utomo, 2023;Wijayanto et al, 2023). Students' creative thinking skills have been fulfilled by applying the PBL model in the learning process (Sahida, 2018).…”
Section: Implementation Of Problem Based Learning On Creative Thinkin...mentioning
confidence: 99%
“…An Technological Literacy on Virus Material JEP (Jurnal Eksakta Pendidikan) |Vol 7| No 2| 185-196 increase was obtained from the average results of creative thinking skills with the application of conventional learning of 64.07, while the application of Problem Based Learning amounted to 75.81. Other research also states that PBL can develop students' creative thinking skills (Utomo, 2023;Wijayanto et al, 2023). Students' creative thinking skills have been fulfilled by applying the PBL model in the learning process (Sahida, 2018).…”
Section: Implementation Of Problem Based Learning On Creative Thinkin...mentioning
confidence: 99%
“…Previous research on problem-based learning is effective in encouraging students' creative thinking skills in learning (Wijayanto et al, 2023;(Adiilah &;Haryanti, 2023;Khoiri et al, 2023). The research gap is that many studies on problem-based learning models have not found a measure of the impact of IoT-based problem-based learning models on students' creative thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the outcomes of the study comprehensively, a combination of quantitative and qualitative research methods will be employed. Pre and post-assessments will be conducted to measure students' progress in various language skills, including vocabulary recognition, sentence construction, and reading comprehension (Wijayanto et al, 2023). Furthermore, surveys, interviews, and classroom observations will provide insights into students' attitudes, motivation, and perceptions towards the use of simple translation as a language learning tool.…”
Section: Introductionmentioning
confidence: 99%